TEACHING ENGLISH FOR EFL YOUNG LEARNERS USING TASK BASED LANGUAGE TEACHING - Nurbani Nurbani (ICoTE Proceedings)
In Indonesia, English is a foreign language which taught in school. For the EFL especially young learners, English is not common for them. It will be a quite challenging for teacher to motivate them involved in the classroom activities. This article attemps to share an overview of Task Based Language Teaching, the concept of Task Based Language Teaching it self and the example how its applied in teaching English for EFL young learners. The writer has tried to apply this method to the fifth grade students of primary school. The subject is fifth grade students. The selection of activities or tasks for the students were based on the students’ need in order to motivate students so they can engage their attention, improve intellectual and linguistic challenge and promote their language development. After applied this method in the classroom activities, the writer found that the students more interested with the subject because the task were based on their needs. It also motivates them to learn English because they can finish the task together in group work so they can share their knowledge fulfill the goal of task.